Liberalisation: A review of social dimensions - Pandhe, M.K. (1996)
With a background on occasioning of liberalisation in India and revealing true meanings of its global thrust, the author reviews social dimensions of its impact on India as reflected in the negative feature emerging from operationalisation of some of its components: (1) extension of social clause in international trade pertaining to prohibiting child labour and adherence to ILO Conventions; (2) exit policy; and (3) disinvestment and privatisation along with the phenomenon of rising corruption. He concludes with a call for timely correctives. - Reproduced
Keywords: Liberalization - India; Economic liberalization